Histoire du droit et « théorie du gender ». Les approches critiques du genre - Pierre-Anne Forcadet (Criminocorpus, 2025)
The article aims to confront gender studies with their critics that come from legal historians based upon a so-called “gender theory”. The scientific legitimacy itself is often questioned with accusation of lack of objectivity, but the debate lies essentially around the neo-jusnaturalism of most of the authors defending a symbolical order, that enters in contradiction with modern society and the recent turn in favour of gender studies in french legal history.